Urgensi Pendidikan Camat Selaku PPAT Sementara dalam Mencapai Nilai Keadilan - Sulkifli, Sulkifli; Fadhilah, Naily (UI Scholars Hub, 2023)
The position of PPAT in its implementation does not rule out the possibility of a vacancy due to the vast territorial area of Indonesia, so that a temporary PPAT is needed, in this case the sub-district head or village head. Temporary PPAT generally has the same duties and authority as PPAT. However, in practice, in carrying out their duties and authority they often make mistakes. This is because not all sub-district heads appointed as temporary PPATs have a legal education background or knowledge about PPATs. The purpose of writing this article is to understand the process of appointing a sub-district head as a temporary PPAT and to analyze the urgency of educating a subdistrict head as a temporary PPAT in achieving the value of justice. The conclusion obtained in this research is that the education of the sub-district head as a temporary PPAT needs to reflect justice, because justice will be realized if the division of work is in accordance with his talents and areas of expertise. This is how important it is to educate the Subdistrict Head as a Temporary PPAT for three reasons, namely, 1) The appointment of a Temporary PPAT Subdistrict Head does not go through qualifications like a PPAT appointment, 2) Increasing human resources as a Temporary PPAT, 3) The urgency of authenticating the deed.